Form as Social Commitment: The art of Giovanni Anselmo during the Anni di Piombo (ENTHYMEMA, 2012)
In April 1968, concurrent with the early stages of the student movement in Europe, the young Arte Povera artist Giovanni Anselmo installed his first solo exhibition at a Turin gallery. The sculptures shown there were not static objects, but rather demonstrations of invisible concepts like relativity. What emerged in Anselmo‘s first solo show and developed over the ensuing decade was a tactical resistance to the crystallization of his works into a single image or static object. This paper argues that this approach was also central to a critical understanding of the roles of the artist and the viewer during a time of great political foment in Italy and throughout Europe. I explore the relationship of Anselmo‘s sculptural interests to the currency of phenomenology in Northern Italy, the theorization of Arte Povera, in which he figures as a central protagonist, as well as to the socio-political challenges of the 1970s in Italy. Between 1967 and 1978, Anselmo endeavored to reveal tense fullness in empty spaces and to discover latent energy in seemingly inert materials by activating the viewer‘s ability to recognize them as small indications of a dynamic macrocosm. In the context of 1968 and the ensuing Anni di piombo, such macrocosmic glimpses might occasion a broadened worldview, in which the closed perceptual dialectic of self versus world could expand to include other, previously invisible, possibilities. From this expanded point of view prompted by Anselmo‘s presentation of energies, one can begin to understand, and even undermine, man-made ‗invisible‘ systems like government and class. By doing this through the form of the work rather than its explicit content, Anselmo models the notion of an artist using form as social commitment. This mode of working has resonance for many artists today, who may struggle with reconciling their material practices with political allegiances in an increasingly co-opted art market.
Keywords: Anselmo; Arte povera; sculpture; anni di piombo